RELATIONSHIP BETWEEN RADIOLOGICAL ANATOMY OF THE STOMACH AND SOMATOTYPE - Dilshod K. Khudoiberdiev (Central Asian Journal of Medicine, 2025)
According to statistics, as of January 1, 2022, one of the highest rates of diseases diagnosed for the first time in the population is associated with diseases of the digestive system, and it is observed that the number of these diseases has reached 11 thousand per 100 thousand of the population. Chronic gastritis accounts for 60-85% of stomach diseases and increases by 1.4% annually. In European countries, 2-5% of the adult population suffers from gastric ulcer. If you look at the studies conducted by scientists, it was noted that ulcers and changes in the wall of the stomach and duodenum account for 8-10% of the total number of biopsies, and sometimes 20%. To date, acute erosions of the mucous membrane are detected in 3-9 percent of patients with this disease during examination, and this condition is considered one of the aspects of diagnosis that requires special attention. Purpose of the work. A detailed study of digestive tract diseases requires the development of individual preventive and treatment measures for each patient, especially in childhood, it is necessary to pay attention to the structure of the mucous membrane of the digestive system wall. Currently, methods of radiation diagnostics and prognosis are being improved, this method is high-quality, does not cause difficulties and does not cause secondary diseases in the patient.